I. U. Niemcewicz Sekretarz Stanu, Prezes Towarzystwa przyjaciół nauk. - Mielcarzewicz, Teofil (1807-1879) (Poznań i Berlin w Litografii K.A. Simona, 1829)
Przedstawia J.I. Niemcewicza, popiersie 3/4 w prawo, głowa na wprost.